Building customer loyalty in retail banking: a serial-mediation approach. Issue 2 (3rd October 2019) - Kamath, Pallavi R.; Pai, Yogesh P.; Prabhu, Nandan K.P.
Abstract : Purpose: The purpose of this paper is to advance research on the relationship between customer experience and customer loyalty by exploring the serially mediating roles of brand equity and customer satisfaction and the moderating roles of age, gender, education and family income in the retail banking industry. Design/methodology/approach: A total of 500 responses of retail banking customers were used to test the model using the partial least squares structural equation modeling approach. Advanced statistical techniques, such as importance-performance map analysis and a joint application of FIMIX-PLS and PLS-POS, were used to gain new insights. Findings: The study highlighted that the relationship between customer experience and loyalty is serially mediated by brand equity and customer satisfaction. Age, gender and education were found to be significant moderators in the customer experience–loyalty relationship. Age and gender were found to be significant moderators in the brand equity–loyalty relationship. Practical implications: The study strongly suggests that practitioners not only focus on delivering exceptional customer experiences but also on providing leverage brand equity and satisfaction to build customer loyalty. Practitioners should focus on training their front-line employees to improve the quality of their behavior and relations with customers and thereby build customer loyalty. Originality/value: To the authors' knowledge, this is the first study to explore the mediating role of several variables sequentially and the moderating role of customer demographics in the customer experience–customer loyalty relationship.